Analisis Pengaruh E-Commerce: Studi Literatur Terhadap Pertumbuhan Ekonomi UMKM - Sadrakh Zefanya Putra; Shasabila Titanie Harianto; Yabes Christian Matondang (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
In this modern era, we can find the influence of technology on every line of life. One form of technology that we often encounter is e-commerce. E-commerce emerged as a form of progress from buying and selling places that we usually call markets. This e-commerce has many advantages that we cannot find when we are in conventional markets. Therefore, most people who act as consumers choose e-commerce over visiting conventional markets. However, the emergence of e-commerce will have an impact on MSMEs. MSMEs that stand as community small businesses can experience fluctuations in dynamic changes in economic growth. Therefore, this research will be carried out. The research method to be carried out is to use the Systematic Literature Review (SLR). By using journal references and research that has been done, decisions will be made in accordance with the issues raised. This research itself was conducted with the aim of: 1) Seeking influence from e-commerce which has a big impact on MSMEs and 2) Finding solutions that are beneficial to both parties.